The association of genetic variants in FGFR2 with osteoporosis susceptibility in Chinese Han population - Yang, Yang (Biosci Rep, 2019)
Objective: The present study was conducted for exploring the influence of fibroblast growth factor 2 receptor (FGFR2) gene polymorphisms on osteoporosis occurrence risk in the Chinese population. Methods: Polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) was conducted for the genotyping of polymorphism in 145 osteoporosis patients and 123 controls. The status of Hardy–Weinberg equilibrium was detected in the control group. Genotype and allele frequency comparison of polymorphism between the two groups was performed by χ(2) test, odds ratio (OR) with 95% confidence interval (95% CI) was used for the result expression about the association of FGFR2 polymorphisms with osteoporosis. Furthermore, the results were adjusted by clinical features via logistic regression analysis. Results: AA genotype and A allele of rs2420946 were significantly associated with the increased risk of osteoporosis development adjusted by clinical features (OR = 2.238, 95% CI = 1.055–4.746; OR = 1.482, 95% CI = 1.042–2.019). Similarly, CC genotype and C allele frequencies of rs1219648 were detected the significant difference between the case and control groups (P<0.01); moreover, it was still significant by the adjustion of clinical features, which indicated that rs1219648 was significantly associated with the risk of osteoporosis occurrence (OR = 2.900, 95% CI = 1.341–6.271; OR = 1.602, 95% CI = 1.126–2.279). Haplotype T-A-C-T also obviously increased the occurrence risk of osteoporosis (OR = 1.844, 95% CI = 1.180–2.884). Besides, the significant interaction of FGFR2 polymorphisms with drinking status in osteoporosis was also found (P<0.05), especially rs2981579. Conclusion: FGFR2 rs2420946 and rs1219648 polymorphisms may be the risk factor of osteoporosis in Chinese population. Furthermore, the interaction of FGFR2 polymorphisms with drinking may play an important role in osteoporosis etiology.